2018
DOI: 10.1242/bio.035204
|View full text |Cite
|
Sign up to set email alerts
|

Physiological electric field works via the VEGF receptor to stimulate neovessel formation of vascular endothelial cells in a 3D environment

Abstract: Electrical stimulation induces significant neovessel formation in vivo. We have shown that electrical stimulation of endothelial cells functions as an important contributor to angiogenesis in monolayer culture. Because angiogenesis occurs in a three-dimensional (3D) environment, in this study we investigated the effects of a direct current (DC) electrical field (EF) on endothelial neovessel formation in 3D culture. There was a significant increase in tube formation when endothelial cells were stimulated with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
4
29
1
Order By: Relevance
“…This may be attributed to the surface charge of the polarized nanocomposite membranes, which could stimulate vascular endothelial cell differentiation and promote neovascularization in vivo, as reported previously 41. Our results were also consistent with other studies, which showed that exogenous electrical stimulation,41,42 an external electric field,43,44 or even charged scaffold material,45 could induce vascular endothelial cell luminal formation in vitro and neovascularization in vivo. Early neovascularization had a profound effect on subsequent bone remodeling and bone maturation.…”
Section: Resultssupporting
confidence: 92%
“…This may be attributed to the surface charge of the polarized nanocomposite membranes, which could stimulate vascular endothelial cell differentiation and promote neovascularization in vivo, as reported previously 41. Our results were also consistent with other studies, which showed that exogenous electrical stimulation,41,42 an external electric field,43,44 or even charged scaffold material,45 could induce vascular endothelial cell luminal formation in vitro and neovascularization in vivo. Early neovascularization had a profound effect on subsequent bone remodeling and bone maturation.…”
Section: Resultssupporting
confidence: 92%
“…In conclusion, the present study provides evidence that a physiological level of DC EF stimulates the angiogenic phenotypes of endothelial cells via endothelial NO production, thereby extending our previous findings [18][19][20][21]. We suggest that the downstream components of the VEGF/VEGFR2 signaling pathway, PI3K/Akt-eNOS, are involved in these responses.…”
Section: Discussionsupporting
confidence: 89%
“…For example, an in vivo study by Kanno et al [16] demonstrated that electric field (EF)-stimulated contraction of skeletal muscles can lead to an increase in neovessel formation and VEGF production; Nagasaka et al [17] reported that treatment of rat skeletal muscle with low-level electrical stimulation, which does not cause contraction, was very effective in inducing significant angiogenesis. In vitro, EFs play a vital role in endothelial angiogenic processes including cell migration, elongation, alignment, and tube formation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been performed that test different methods of stimulating new vessel formation into the tissue engineered constructs (reviewed in [104]). Several studies, in dermal wounds, have demonstrated EStim's ability to stimulate new vessel ingrowth from pre-existing blood vessels in adjacent tissues into ischemic wounds [105][106][107][108][109]. DC EStim was shown to promote important angiogenic responses of vascular endothelial cells and selectively regulate production of growth factors and cytokines important in angiogenesis through a feedback loop mediated by VEGF receptors [110,111].…”
Section: Vascularizationmentioning
confidence: 99%